Mine-ness, Other, World. Comparative analysis of Charles Taylor’s and Martin Heidegger’s philosophy - Hładyłowicz, Joanna (Hybris, 2022)
This article is a comparative analysis between Charles Taylor's and Martin Heidegger's philosophy focusing on three main terms: mine-ness, other and world. It is a search for similarities and differences between these terms. In the view of results, mine-ness appears to be the most similar aspect of these two philosophies. It is a core term used for describing both Dasein and self. Close similarities have been marked for the "world" as well. These parallels are based on philosophers understanding of this word, of what it means to "self" and how this includes "others". The article is divided into three parts, each dedicated to one of the main themes of this work. Concluding, although there are some similarities and differences between Taylor's and Heidegger's philosophies and that there is a significant time gap between the main works concerning discussed in this article issues, what makes them most alike is how still up-to-date these philosophies are.